BAT402 – Fisheries Management (Pengurusan Perikanan) July/August 2023 - Pusat Pengajian Sains Kajihayat, PPSK (2023)
Second Semester Examination 2022/2023 Academic Session July/August 2023 BAT402 – Fisheries Management (Pengurusan Perikanan) Duration : 2 hours (Masa : 2 jam)